Water technology, knowledge and power. Addressing them simultaneously. (1st November 2017) - Aubriot, Olivia; Fernandez, Sara; Trottier, Julie; Fustec, Klervi
Abstract : This review focuses on how water knowledge and technology are linked to power relations when they shape water access, sharing, and distribution. It examines how scholars have tackled this issue explicitly or implicitly. To do this, the paper first discusses the way knowledge and technology are intimately intertwined. Since knowledge and technology are never produced in a sociopolitical vacuum, it goes on to discuss how they embed and produce power relations. This article particularly highlights the way the concept of co‐production has been used to address these issues by focusing on how boundaries and categories are made. Lastly, the review suggests four lines of research to further explore co‐production processes: (1) understanding the political construction of scales of water use and access; (2) identifying the diversity and dynamics of the relations toward water that societies deploy, (3) grasping the way framings and paradigms have been historically shaped, and (4) pursuing the simultaneous analysis of the political and material dimensions of water. WIREs Water 2018, 5:e1261. doi: 10.1002/wat2.1261 This article is categorized under: Human Water > Water Governance Human Water > Water as Imagined and Represented Abstract : Water knowledge and technology shape the way water is accessed, shared and distributed. Therefore the research question is: how to address their link to power relations? Here in the photograph, groundwater irrigation in South India